Desenvolvimento de um programa de recebimento, separação e correta destinação de resíduos sólidos (pilhas e baterias) nos ônibus municipais de uma empresa de transporte coletivo urbano - Tamura, Jorge Yoshio (2009)
This project deals with the development of a program for the reception, separation and correct destination of solid residues (used disposable and rechargeable batteries) in the buses of a company of collective transport of the city of Colombo, located in the metropolitan region of Curitiba, Paraná. In the process of development of the program, the students of the Experimental Office of the Design Course - ED and the students of the Experimental Advertising Agency - Practice, both of the Positivo University, had created a personage symbol for the program, the label, posters, folders and the whole advertising campaign for the spreading of the program. The program for the reception, separation and correct destination of solid residues (used disposable and rechargeable batteries) in the buses of the Viação Colombo bus company received the name of Programa Energia Positiva, because it has adopted a strategy of development of an emotional and informative campaign, in order to convince in such a way either on the positive aspects of the recycling and also on the importance and advantages to discard correctly this type of residue. A collector of used disposable and rechargeable batteries was developed and manufactured, painted with showy colours, similar to the personage symbol of the Programa Energia Positiva, for the installation inside the buses. The use of a showy collector aimed to awake the interest of the passengers for the questions related to the campaign. A pilot test was carried through, where forty and four collectors had been installed in twenty and two buses during a period of six months and in this period, all the buses had been monitored daily. At the end of the sixth month there had been collected, approximately 1,200 kg of used disposable and rechargeable batteries in these twenty and two buses, that only represent twenty percent of the total fleet of the Viação Colombo bus company, and taking in account the expressive results that had been gotten, collectors are being installed in all the buses of the fleet.